Every case is different: Cautionary insights about generalisations in human-wildlife conflict from a range-wide study of people and jaguars. (August 2021) - Zimmermann, Alexandra; Johnson, Paul; de Barros, Alan Eduardo; Inskip, Chloe; Amit, Ronit; Soto, Erika Cuellar; Lopez-Gonzalez, Carlos A.; Sillero-Zubiri, Claudio; de Paula, Rogerio; Marchini, Silvio; Soto-Shoender, Jose; Perovic, Pablo G.; et al.
Abstract: Throughout their range, jaguars ( Panthera onca ) are persecuted for killing livestock, posing a widespread and serious threat to their survival. Human-jaguar conflict occurs across a very large variety of geographic, agronomic and socio-economic contexts and across heterogeneous communities. We conducted seventeen case studies across seven countries in central and south America to search for patterns in socio-economic predictors of human-jaguar conflict that could help up-scale management of this range-wide jaguar conservation challenge. Our study revealed that within and across case studies there were considerable differences in farmers' education levels, economic dependence on livestock, personal experience with livestock losses, as well as tolerance of and attitudes and social norms towards jaguars. Among this diversity, we sought common predictors of tolerance of jaguars, but found that no quantifiable single contextual factor could be used to predict how farmers perceive jaguars and deal with depredation. While patterns did exist within individual case studies, none of these were consistent across a majority of cases. We conclude that observations of patterns in human-wildlife conflict are valid only for informing action at a local scale, and even if a small number of case studies appear to show similar patterns this does not make the observation universally true. It is important to remember not to generalise from case studies. Nevertheless, although each case is likely to require individual solutions, insights from aggregate or wide-range studies can provide insights into the range of possible scenarios, adding breadth of information to depth of local knowledge. Highlights: Human-jaguar conflict across the species range occurs in many different socio-economic contexts. Every case of conflict is unique, even when natural, economic or cultural settings appear similar. No consistent factors could be found that predict how farmers perceive jaguars and deal with losses of livestock. We caution that case study research should not be used to inform conflict mitigation at large scale. Each conflict must be understood individually, without generalisation from case-specific observations.